Belize : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The erosion of EU trade preferences for bananas and sugar will have immediate negative implications for Belize's economy. This paper suggests ways to enhance public debt management in Belize. The vulnerability of the banking sector appears relatively modest. However, the current level of loan-loss provisions and collateral valuation rules are not up to the international standards. Important steps have been taken to further improve compliance with the Basel Core Principles. The importance of debt-service reduction through sound macroeconomic policies is highlighted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet